Increasing Reading Interest and Reading Literacy Skill Through the GEMALISTA School Literacy Movement in Elementary Schools (Current Research in Education: Conference Series Journal, 2024)
This research aims to describe the reading literacy movement, known as the Gemalista Program, at Ciulu 2 State Elementary School (SDN 2 Ciulu) for increasing students' reading interest and literacy skills. Employing an Action Research model with a qualitative approach, data collection utilized triangulation techniques (interviews, observations, and documents) alongside survey data for samples. The development of a literacy culture was structured in three stages: (1) planning (goal, program, strategy, and infrastructure formulation), (2) implementation (through processes of habituation, development, and teaching), and (3) evaluation (weekly, monthly, and annual). Based on the results of the Project Management Office (PMO) 1 school level which followed four stages: reflection, root of the problem, fix, and solution it was evident that students' reading interest and literacy skills required improvement. The proposed solution involves implementing a habituation program (a 15-minute reading activity before or after learning), a development program (via non-academic activities, extracurriculars, and library visits), and a learning program that incorporates literacy strategies with differentiated learning techniques in shared, guided, and independent reading. The research concludes that the implications of developing the Gemalista Program successfully increase the reading interest and reading literacy skills of students at SDN 2 Ciulu.